2021
DOI: 10.1111/pbr.12936
|View full text |Cite
|
Sign up to set email alerts
|

Variation in persistency, postdrought recovery and root characteristics in a tall fescue germplasm under interactive effects of exogenously applied salicylic acid and water stress

Abstract: This study was performed for a better understanding of genotypic responses of a germplasm of tall fescue to different prolonged drought stresses and exogenously applied salicylic acid (SA) in terms of drought tolerance, postdrought recovery, persistence and root‐related traits. Twenty‐one diverse tall fescue genotypes were evaluated under three irrigation treatments (IT) (normal, mild and intense drought stress) and the presence of two SA concentrations (0 and 1 mM) during 2015–2017. In the fourth year (2018),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 59 publications
(73 reference statements)
1
0
0
Order By: Relevance
“…The positive relationship between STS and RR under drought stress conditions showed that selection based on higher STS may lead to genotypes with higher RR and drought tolerance. Similar to our findings, positive relationships have been reported between recovery rate and drought tolerance index in tall fescue under drought stress conditions 45 . Yield stability and the high recovery rate after long drought can be important goals in the breeding programs in perennial grasses under drought stress environments 11 .…”
Section: Discussionsupporting
confidence: 92%
“…The positive relationship between STS and RR under drought stress conditions showed that selection based on higher STS may lead to genotypes with higher RR and drought tolerance. Similar to our findings, positive relationships have been reported between recovery rate and drought tolerance index in tall fescue under drought stress conditions 45 . Yield stability and the high recovery rate after long drought can be important goals in the breeding programs in perennial grasses under drought stress environments 11 .…”
Section: Discussionsupporting
confidence: 92%